Clinical characteristics and outcomes in young patients with myocardial infarction. (14th October 2021) - Lv, J; Zhao, Q; Ni, L; Yang, Y; Xu, H
Abstract: Background: Young people hold a stable or increasing percentage of patients with acute myocardial infarction in many countries. However, data on clinical characteristics and outcomes in young patients are lacking. Purpose: To compare clinical characteristics and outcomes between patients aged ≤45 years and those aged >45 years with acute myocardial infarction. Methods: A total of 24125 patients with acute myocardial infarction between January 2013 and September 2014 from China Acute Myocardial Infarction (CAMI) registry were included in this study. Clinical characteristics, in-hospital and 2-year outcomes were compared between patients aged ≤45 years (young) and those aged >45 years (older). Gender disparity in prognosis of myocardial infarction was analyzed among young patients. Results: Of 24125 patients, 2042 (8.5%, 116 female) were aged ≤45 years. Compared with patients aged >45 years, young patients were more often male, current smokers, having medical history of hyperlipidemia and family history of premature coronary artery disease. Young patients were significantly more likely to have clear trigger factor, present with persistent chest pain and suffer ST-segment elevation myocardial infarction. Symptom onset to admission time was shorter in patients aged ≤45 years. For patients undergoing emergency coronary angiography, those aged ≤45 years were more likely to suffer left anterior descending coronary artery related myocardial infarction. Young patients were significantly more likely to receive percutaneous coronary intervention and other medications at discharge, including dual antiplatelet therapy, statins, angiotensin converting enzyme inhibitors or angiotensin II receptor blockers and β blockers. Compared with patients aged >45 years, young patients experienced significantly lower in-hospital and 2-year mortality and major adverse cardiac and cerebrovascular events (MACCE, a composite of death, reinfarction and stroke) rates (Table 1). Among young patients, women experienced higher in-hospital mortality and MACCE rates than men (Table 2). Women who survived at discharge experienced significantly higher 2-year mortality (1.4% vs 3.8%, Log-rank P=0.0412, Table 2). Conclusions: Compared with the older patients, young patients were more likely to present with typical symptoms and receive guideline-recommended medications. Clinical outcomes of patients aged ≤45 years were significantly better than older patients. However, our results showed significant gender disparity in both short- and long-term outcomes of young patients. More efforts are needed to improve prognosis in young patients with acute myocardial infarction. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Twelfth Five-Year Planning Project of the Scientific and Technological Department of China